Improved performance comparisons of radioxenon systems for low level releases in nuclear explosion monitoring. (November 2017) - Haas, Derek A.; Eslinger, Paul W.; Bowyer, Theodore W.; Cameron, Ian M.; Hayes, James C.; Lowrey, Justin D.; Miley, Harry S.
Abstract: The Comprehensive Nuclear-Test-Ban Treaty bans all nuclear tests and mandates development of verification measures to detect treaty violations. One verification measure is detection of radioactive xenon isotopes produced in the fission of actinides. The International Monitoring System (IMS) currently deploys automated radioxenon systems that can detect four radioxenon isotopes. Radioxenon systems with lower detection limits are currently in development. Historically, the sensitivity of radioxenon systems was measured by the minimum detectable concentration for each isotope. In this paper we analyze the response of radioxenon systems using rigorous metrics in conjunction with hypothetical representative releases indicative of an underground nuclear explosion instead of using only minimum detectable concentrations. Our analyses incorporate the impact of potential spectral interferences on detection limits and the importance of measuring isotopic ratios of the relevant radioxenon isotopes in order to improve discrimination from background sources particularly for low-level releases. To provide a sufficient data set for analysis, hypothetical representative releases are simulated every day from the same location for an entire year. The performance of three types of samplers are evaluated assuming they are located at 15 IMS radionuclide stations in the region of the release point. The performance of two IMS-deployed samplers and a next-generation system is compared with proposed metrics for detection and discrimination using representative releases from the nuclear test site used by the Democratic People's Republic of Korea. Highlights: A new approach is proposed for comparing performance of radioxenon systems. Low-level releases are the new real-world challenge for radioxenon systems. The approach augments MDC values with a measure of sensitivity to isotopic ratios. Next-generation systems perform better than currently deployed systems.